Penerapan SMK3 untuk Mencegah Penyakit Akibat Kebisingan di Stasiun Sterilizer pada Pabrik Kelapa Sawit - Mahyunis Mahyunis; Muhammad Syukri; Boby Surya Bimantoro (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
Palm Oil Mill (POM) is a plantation company that specializes in palm oil commodities with outputs in the form of CPO (Crude Palm Oil) and PK (Palm Kernel). 12 processing stations at XYZ POM have high levels of noise, one of which is the sterilizer station which can cause hearing impairment to operators. This study aims to determine the level of noise at the sterilizer station, diagnose hearing impairment due to noise based on audiometry results, and assess the effectiveness of the implementation of the occupational health and safety management system at XYZ POM. The research method used in this study is a quantitative descriptive method using primary and secondary data. From the results of this study, it was found that the calculation of the noise level for 24 hours reached 94.9 dB. This value exceeds the threshold value for noise based on the Regulation of the Minister of Labor and Transmigration No. PER.13/MEN/X/2011 regarding the Threshold Value of Physical and Chemical Factors in the Workplace. To improve the safety and health of employees, XYZ POM implements an Occupational Health and Safety Management System (OHSMS) using the HIRARC (Hazard Identification Risk Assessment and Risk Control) method to identify potential hazards, assess risks and control them, one of which is noise by conducting regular audiometry examinations. The results of the audiometry examination on the sterilizer operator showed normal results. The implementation of the OHSMS at XYZ POM is effective, especially in controlling noise by Government Regulation No. 5 of 2012 regarding the Implementation of the Occupational Health and Safety Management System.